Bite the Bullet: Experiences in Writing Undergraduate Theses during the Covid-19 Pandemic - Wulandari, Bunga Ayu; Ridha, Ahmad; Azzahra, Aulia (Universitas Jambi, Indonesia, 2024)
This research took a closer look at data from an Indonesian public university database that showed that, as of November 2022, 14,44% of English department final-year students from 2017 in a teacher training and education faculty were still working on their theses. Data was gathered through qualitative research using document analysis and interviews to examine the topics, methodologies, and students' experiences writing an undergraduate thesis. The findings showed that the students' theses covered seven topics: teaching and learning, English skills, discourse analysis, sociolinguistics, translation, content analysis, and research and development (R & D). This research found factors contributing to students' challenges in completing their thesis writing during the COVID-19 pandemic, including students' relationships with supervisors, failure to focus, lack of motivation, and difficulties locating relevant references. Additionally, the students used several strategies to help finish their theses on time, for example, setting specific goals, having a study partner, and reading various related sources. This research adds to the body of knowledge on undergraduate students' difficulties and the strategies used in completing their theses during the pandemic. This research is expected to provide insight into possible interventions to assist students in overcoming the difficult task of writing a thesis, primarily when most of the research process is still online.